POLICIES AND PRACTICES RELIGIOUS MODERATION IN PESANTREN - Athoillah, Mohamad; Rahman, Ahmad Syaeful; Firdaus, Aep Syaefudin; Septiadi, Muhammad Andi (Jurnal Pendidikan Islam, 2024)
Pesantren holds a significant position in Indonesia's educational system, functioning as key institutions for religious education and cultural preservation. This study aims to examine the implementation of religious moderation policies within pesantren to encourage interfaith understanding and collaboration among diverse religious groups in Indonesia. Using a mixed-methods approach, the research gathered data from interviews, surveys, and document analysis across a range of pesantren in Indonesia. Findings reveal multiple initiatives to foster religious moderation, including incorporating interfaith education into curricula, enhancing students' critical thinking skills, and promoting gender equality practices. These efforts have been met with successes and challenges; while students benefit from a broader perspective, obstacles such as resource limitations, cultural norms, and resistance to change were notable. This study underscores the vital role of pesantren in promoting religious moderation, which is crucial for nurturing understanding and peace among Indonesia’s religious communities. These findings offer meaningful insights for policymakers, educators, and community leaders on advancing religious tolerance and empathy within Islamic education, supporting the development of a more inclusive and cohesive society.